Investigation of SOA Amplifier Performance of 40 * 10 GB/s DWDM System with 50 GHz Channel Spacing - Husam A. Wahhab, Ahmed A. Amer, Maysoon H. Ismaail (International Journal of Advanced Science and Technology, 2020)
In this study, transmission performance of Semiconductor Optical Amplifier (SOA) in 40*10Gb/s Dense Wavelength Division Multiplexing (DWDM) at channel spacing of 50 GHz is investigated. The measured values of (Q factor, BER, output power) are evaluated by varying the distance of optical fiber of acceptable value (25-300) Km at (-20) dBm minimum input power. The best result is achieved for the system data rate transmission of (400) Gb/s, with the maximum Q factor of (22.21) dB for lower input power (-20) dBm at (50) Km transmission distance. Also, the maximum fiber length of up to (250) km corresponding to less than (10E-12) BER is achieved.